Ocean acidification modulates the incorporation of radio-labeled heavy metals in the larvae of the Mediterranean sea urchin Paracentrotus lividus. (October 2018) - Dorey, Narimane; Martin, Sophie; Oberhänsli, François; Teyssié, Jean-Louis; Jeffree, Ross; Lacoue-Labarthe, Thomas
Abstract: The marine organisms which inhabit the coastline are exposed to a number of anthropogenic pressures that may interact. For instance, the accumulation of toxic metals present in coastal waters is expected to be modified by ocean acidification through e.g. changes in physiological performance and/or elements availability. Changes in bioaccumulation due to lowering pH are likely to be differently affected depending on the nature (essential vs. non-essential) and speciation of each element. The Mediterranean is of high concern for possible cumulative effects due to strong human influences on the coastline. The aim of this study was to determine the effect of ocean acidification (from pH 8.1 down to −1.0 pH units) on the incorporation kinetics of six trace metals (Mn, Co, Zn, Se, Ag, Cd, Cs) and one radionuclide ( 241 Am) in the larvae of an economically- and ecologically-relevant sea urchin of the Mediterranean coastline: Paracentrotus lividus . The radiolabelled metals and radionuclides added in trace concentrations allowed precise tracing of their incorporation in larvae during the first 74 h of their development. Independently of the expected indirect effect of pH on larval size/developmental rates, Paracentrotus lividus larvae exposed to decreasing pHs incorporated significantly more Mn and Ag and slightly less Cd. The incorporation of Co, Cs and 241 Am was unchanged, and Zn and Se exhibited complex incorporation behaviors. Studies such as this are necessary prerequisites to the implementation of metal toxicity mitigation policies for the future ocean. We discuss possible reasons and mechanisms for the specific effect of pH on each metals. Graphical abstract: Image 1 Highlights: The radionuclide method allowed accurate tracing of the metal incorporation within this microscopic planktonic species. Metal incorporation in sea urchin larvae strongly correlates with the indirect delaying effect of acidification on larval size. Independently of the size effect, acidification directly affects the incorporation behavior of four metals (Mn, Ag, Se, Zn). The nature of the modulation is specific to each metallic element (see graphical abstract). Relationships between speciation, bioaccumulation and toxicity in the context of changing seawater pH requires more research.